2020
DOI: 10.3390/ijerph17093334
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Trend Study of Tuberculosis Incidence in China, India and United States 1992–2017: A Joinpoint and Age–Period–Cohort Analysis

Abstract: Tuberculosis (TB) is one of the major infectious diseases with the largest number of morbidity and mortality. Based on the comparison of high and low burden countries of tuberculosis in China, India and the United States, the influence of age-period-cohort on the incidence of tuberculosis in three countries from 1992 to 2017 was studied based on the Global burden of Disease Study 2017. We studied the trends using Joinpoint regression in the age-standardized incidence rate (ASIR). The regression model showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…The RRs of these two age groups were nearly the same (RR = 2.0). From a wider perspective, young adults (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and the elderly (50-84) were TB notification risk populations in mainland China. Unlike the bimodal distribution of the TB notification risk, the TB mortality risk increased monotonically with age and sharply increased from the age of 50.…”
Section: Age Period and Cohort Effectsmentioning
confidence: 99%
“…The RRs of these two age groups were nearly the same (RR = 2.0). From a wider perspective, young adults (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and the elderly (50-84) were TB notification risk populations in mainland China. Unlike the bimodal distribution of the TB notification risk, the TB mortality risk increased monotonically with age and sharply increased from the age of 50.…”
Section: Age Period and Cohort Effectsmentioning
confidence: 99%
“…Previous studies revealed that age is a vital factor of TB incidence, and ageing may lead to a continuous increase in the risk of TB [ 15 ]. Gender is considered to be another factor implicated in TB incidence, and TB is more common in males than females [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been no recent systematic data published on changes of disease burden and regional disparities of TB in China, except for some studies which reported overall incidence trends [ 11 , 12 ]. The current study aims to examine changes in newly notified and newly smear-positive cases of TB in different regions of China based on national routine surveillance data from 1997 to 2018, and to assess the effectiveness of the TB control program in China.…”
Section: Introductionmentioning
confidence: 99%